KOMPATIBILITAS TRANSFORMASI SISTEM SUBAK DAN AGROEKOWISATA UNTUK MENDUKUNG PENGEMBANGAN KAWASAN - , SUMIYATI, Dr. Ir. Lilik Setiarso, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Subak is a traditional irrigation institutional in Bali, which its function is to manage irrigation water that comes from a specific source. Subak has some weaknesses, as well as several strengths. One disadvantage of subak system is not resistant to the external intervention. Until now Bali is still one of the world tourist destinations. As tourism has been developing, the phenomenon of the youth become a farmer is decreasing and the reduced of paddy fields due to land use conversion. Nowadays, the increase of touristsâ interest and the alternative tourism are the opportunity for subak development. Some efforts are needed to integrate agriculture and tourism, so that Subak is not only an object but able to play a role as a subject. The study of the compatibility of transformation of subak system and agro-ecotourism is necessary to support the regional development. The research was conducted in several steps, which were (1) defined the strategy using SWOT analysis (ii) determined the alternative of subak system development using Analitical Hierarchy Process (AHP) method and (iii) developed the system. Data analyses were performed using some approaches, which are empiric approach, dynamic approach, and fuzzy logic approach and the feasibility analysis. Simulation results on agro-ecotourism business at subak system showed that in the 1 st and 2 nd year, there was no significant benefit achieved, but in 3 rd year of the implementation of agro-ecotourism, this business started to get profits and it continues each year. BEP was accomplished in 3 rd year of its implementation. The value of BC > 1 was achieved in 3 rd year of the implementation of agro-ecotourism and the value of NPV>0 also IRR equal to 1.60%. These conditions suggested that agro-ecotourism is feasible to be implemented. The water utilization level in Subak Anggabaya and Lodtunduh in a year were categorized âgoodâ and the supply of irrigation water was sufficient with the value of RIS indicator in a year was >1. The total area of irrigated land in Subak Anggabaya and Lodtunduh were well-conformed to its planning. The value of physical aspect in Subak Anggabaya is 2.00 (moderate) and the same value for Subak Lodtunduh. Those values were increasing into 2.21 for Subak Anggabaya and 2.23 for Subak Lodtunduh since the agro-ecotourism were implemented. The social condition of the community in subak system to support the development of agro-ecotourism area for Subak Anggabaya was 2.00 (Moderate) while for Subak Lodtunduh was 2.23 (moderate to good). Water quality in subak samples i.e. Subak Anggabaya and Lodtunduh were in good condition as well as Subak Padang Galak and Kertalangu. The value of water quality parameter that was measured showed those values were still below the permitted maximum level for agriculture. Subak Anggabaya and Subak Lodtunduh got 4 (four) in term of management index, which means both have their own transformation potency to support compatibility with agroecotourism. The correlation equation of subak system transformation to encourage with agro-ecotourism for Subak Anggabaya is MPAS = 0,465 EKO + 0,265 TEK + 0,265 SOSMAS + 0,465 LINGK + 0,15 and for Subak Lodtunduh is MPAS = 0,444 EKO + 0,244 TEK + 0,290 SOSMAS + 0,444 LINGK + 0,20. The track condition need to be improved at Subak Anggabaya. At Subak Lodtunduh, awig-awig and perarem would be better if expressed in written form, as soon as the hall of subak and the track condition need to be repaired in the subak transformation to encourage compatibility with agro-ecotourism.